Resources and Capabilities Development of Musicians: The Case of the School of Higher Sacred Music of the Archdioceses of Guadalajar (Global Journal of Management and Business Research, 2013)
The aim of this paper is to analyze the labor market of the musicians in the Archdiocese of Guadalajara, from the resource-based view. It begins with question of what it means to be a musician in Mexican society. The research method used is to review literature in the cultural and labor field. The main conclusion is that the Archdiocese of Guadalajara as a company invests in training human resources for the performance of sacred music and where the labor market for musicians has the behavior of an internal labor market.
Keywords: tangible and intangible resources; labor market; sacred music; archdiocese of guadalajara